The Impact of Service Quality and Promotion on Revisit Intention of Museum Tourism with Customer Satisfaction and Destination Image as Mediating Variables - Diska Dwi Yunanza; Muzakar Isa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study acknowledges its limitations in being confined to the SBY ANI Museum in Pacitan, which restricts the generalizability of findings to other museums or tourist destinations, as visitor experiences and behaviors may vary. Additionally, the use of questionnaires could introduce bias due to self-reporting tendencies and potential overrepresentation of highly satisfied or dissatisfied respondents. The questionnaire's design could be elaborated upon, including whether pre-testing was conducted and whether questions were balanced to avoid ambiguity or leading responses. While Smart PLS was appropriately used for path analysis, the study could enhance clarity by detailing the interpretation of path coefficients, including effect sizes and confidence intervals, to better illustrate the strength and significance of the observed relationships.